“When she goes out, she feels better:” co-designing a Green Activity Program with Hispanic/Latino people living with memory challenges and care partners - Lassell, Rebecca K. F.; Tamayo, Valeria; Pena, Triana A.; Kishi, Misa; Zwerling, Jessica; Gitlin, Laura N.; Brody, Abraham A. (Frontiers in Aging Neuroscience, 2024)
Utilizing a participatory approach, we sought to co-design a 12-week Green Activity Program (GAP) with Hispanic/Latino individuals living with memory challenges and their care partners, local outdoor professionals, and healthcare providers.Methods: Participants were recruited via convenience and snowball sampling in the Bronx, New York with Hispanic/Latino persons living with memory challenges and care partners, outdoor activity professionals, and interdisciplinary healthcare providers/dementia experts. Co-design occurred iteratively with 5 focus groups and 4 individual interviews lasting 30-90 minutes and focused on program and research design. Sessions were recorded and transcribed. Utilizing directed content analysis data was coded using a priori codes program design and research design.Results: 21 participants completed co-design activities: (n=8 outdoor activity professionals, n=6 Hispanic/Latino persons living with memory challenges and care partners, and n=7 interdisciplinary healthcare providers/dementia experts). Participant preferences for program design were captured by subcodes session duration (30-90 minutes), frequency (4-8 sessions), and delivery modes (in-person and phone). Participants' preferred nature activities included group exercise and outdoor crafts [crocheting], outcomes of social participation, connectedness to nature, decreased loneliness, and stewardship were identified. Preferred language for recruiting and describing the program were "memory challenges," "Hispanic/Latino," and "well-being." Referral pathways were identified including community-based organizations and primary care. Co-design was a successful form of engagement for people living with memory challenges that enabled participants to help design key elements of the GAP and research design. Our processes, findings, and recommendations for tailoring co-design to engage Hispanic/Latino people living with memory challenges can inform the development of other programs for this population.